A comparison of microvascular responses to visible and near‐infrared lasers. Issue 6 (29th June 2014) - Li, D.; Farshidi, D.; Wang, G.X.; He, Y.L.; Kelly, K.M.; Wu, W.J.; Chen, B.; Ying, Z.X.
<x xml:space="preserve">Abstract</x> Background and Objective Pulsed dye laser (PDL) is a commonly used treatment for Port Wine Stain birthmarks (PWS). However, deeper components of PWS are often resistant to PDL. Deeper penetrating lasers, including the long pulsed Neodymium:Yttrium Aluminum Garnet (Nd:YAG) laser have been used, but carry greater risk. This study evaluates the distinct blood vessel thermal responses to visible (595 nm) and near infrared (1, 064 nm) lasers using animal and numerical models. Study Design/Materials and Methods Blood vessels in the rodent dorsal skin chamber (DSC) were irradiated by a 595 nm PDL and a long‐pulsed 1, 064 nm Nd:YAG laser. Laser‐induced immediate and 1‐hour post‐structural and functional changes in the vessels were documented. Numerical simulations were conducted using a 1, 000 µm depth SD mouse skin fold to simulate experimental conditions. Results PDL irradiation produced immediate blood vessel hemorrhage. Modeling indicated this occurs due to preferential heating of the superior parts of large blood vessels. Nd:YAG irradiation resulted in blood vessel constriction; modeling indicated more uniform heating of vessel walls. Conclusion PDL and Nd:YAG lasers result in distinct tissue responses. This supports different observable clinical treatment end points when using these devices. Vessel constriction associated with the Nd:YAG may be more difficult to observe and is one reason this device may carry greater risk. Lasers Surg. Med. 46:479–487, 2014. © 2014 Wiley Periodicals, Inc.